STATUS PENGELOLAAN PERIKANAN SIDAT (Anguilla Spp.) BERDASARKAN PADA PENDEKATAN EKOSISTEM DI DAERAH ALIRAN SUNGAI (DAS) CIMANDIRI, JAWA BARAT - Fachri, Faridz Rizal; Arthana, I Wayan; Merit, I Nyoman; Mustofa, Achmad (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science), 2023)
Anguilla spp . is a catadromous fish species that have high export value in supporting the livelihood and food source for the local community in the Cimandiri Watershed, West Java, which is involved in the Indonesian Fisheries Management Area - Inland Waters (WPPNRI-PD) 432. However, pressure on habitat and watershed ecosystems is leading to degradation due to anthropogenic activities is inevitable. This study aimed to determine the composite index of the seven domains and the eel-fishery management status performance based on the EAFM approach in the Cimandiri watershed. The research was carried out from April 2021–February 2022, using a quantitative method focused on testing theory by measuring research variables with numbers and analyzing data based on the findings in each domain. The ex-situ and in-situ data were collected through direct measurements and in-depth interviews with respondents. Subsequently, the composite scores of domains were calculated using flag modeling (multi-criteria analysis). The results highly likely indicated that habitat and social are the lowest-performance domains and require more attention for improvements. In general, the status of the eel fishery management using the EAFM approach in the Cimandiri watershed is fairly good. However, integration of multi-sectoral collaboration is highly needed through the development of effective co-management by maximizing the roles of the community to be further involved in planning and implementing the management actions of the Cimandiri watershed in the form of participative, community-based, toward sustainable use of the resources. Kata kunci: Eel, Cimandiri Watershed, EAFM, C o-management